Why do people access news with mobile devices? Exploring the role of suitability perception and motives on mobile news use. Issue 1 (February 2015) - Shim, Hongjin; You, Kyung Han; Lee, Jeong Kyu; Go, Eun
Highlights Suitability for accessing news is associated with online news reading motivations. Social utility motive is not significant in news use with smartphone or social media. Information seeking is a primary reason for social media news consumption. Mobile news users have the potential to engage in political issues. Mobile media are not distinct from other media offering news.